Cataract Surgery Outcomes in Human Immunodeficiency Virus Positive Patients at a Tertiary Care Academic Medical Center in the United States. (3rd September 2021) - Miller, D. Claire; Patnaik, Jennifer L.; Palestine, Alan G.; Lynch, Anne M.; Christopher, Karen L.
ABSTRACT: Purpose : To compare cataract surgery complications and visual outcomes in patients with and without human immunodeficiency virus (HIV). Methods : A retrospective cohort study was conducted on eyes undergoing phacoemulsification cataract surgery at an academic eye center from 1/1/2014 to 8/31/18. Outcomes included best corrected distance visual acuity (CDVA), intraoperative complications, cystoid macular edema (CME), and persistent anterior uveitis (PAU). Binary outcomes were analyzed using logistic regressions with generalized estimating equations. Visual outcomes were analyzed using a linear mixed model. Results : 9756 eyes from 5988 patients were included in the analysis. Of these, 66 eyes from 39 patients were HIV positive (HIV+). HIV+ patients were significantly younger at the time of surgery than HIV negative patients ( p < .0001). Among HIV+ patients with available lab data, the mean CD4 count was 697.3 (SD = 335.7), and 48.7% of subjects had an undetectable viral load. Five eyes from three HIV+ patients had a history of cytomegalovirus retinitis (CMVR). Positive HIV status was not associated with increased risk of intraoperative complications. Post-operative CDVA was better in the HIV negative group compared to the HIV+ group but not significantly different (about 20/24 vs. 20/28, p = .0829). Eyes from HIV+ patients were at increased risk of developing PAU after surgery (adjusted OR = 6.04, 95% CI: 2.42–15.1, p = .0001), as well as CME (adjusted OR = 3.25, 95% CI: 1.02–10.4, p = .0470). Conclusions : Eyes from HIV+ patients were at greater risk of developing PAU and clinically significant CME; however, HIV+ patients had similar CDVA after cataract surgery compared to HIV negative patients.